Efficiency and Power Limits of Electrical and Tendon-Sheath Transmissions for Surgical Robotics - Wagner, Christopher R.; Emmanouil, Evangelos (Frontiers in Robotics and AI, 2018)
A popular design choice in current surgical robotics is to use mechanical cables to transmit mechanical energy from actuators located outside of the body, through a minimally invasive port, to instruments on the inside of the body. These cables enable high performance surgical manipulations including high bandwidth control, precision position control, and high force ability. However, cable drives become less efficient for longer distances, for paths that involve continuous curves, and for transmissions involving multiple degrees of freedom. In this paper, we consider the design tradeoffs for two methods of transmitting power through an access port with limited cross sectional area and curved paths - tendon/sheath mechanical transmissions and electrical wire transmissions. We develop a series of analytic models examining fundamental limits of efficiency, force and power as constrained by access geometry, material properties, and safety limits of heat and electrical hazards for these two transmission types. These models are used to investigate the potential of achieving the required mechanical power requirements needed for surgery with smaller access ports and more difficult access pathways. We show that an electrical transmission is a viable way of delivering more than sufficient power needed for surgery, highlighting the opportunity for next-generation actuators to enable more minimally invasive surgical devices.